Site-specific manipulation of Arabidopsis loci using CRISPR-Cas9 SunTag systems - Papikian, Ashot; Liu, Wanlu; Gallego-Bartolomé, Javier; Jacobsen, Steven E. (Nature communications, 2019)
Understanding genomic functions requires site-specific manipulation of loci via efficient protein effector targeting systems. However, few approaches for targeted manipulation of the epigenome are available in plants. Here, we adapt the dCas9-SunTag system to engineer targeted gene activation and DNA methylation in Arabidopsis . We demonstrate that a dCas9-SunTag system utilizing the transcriptional activator VP64 drives robust and specific activation of several loci, including protein coding genes and transposable elements, in diverse chromatin contexts. In addition, we present a CRISPR-based methylation targeting system for plants, utilizing a SunTag system with the catalytic domain of the Nicotiana tabacum DRM methyltransferase, which efficiently targets DNA methylation to specific loci, including the FWA promoter, triggering a developmental phenotype, and the SUPERMAN promoter. These SunTag systems represent valuable tools for the site-specific manipulation of plant epigenomes. Few approaches for targeted manipulation of the epigenome are available in plants. Here, the authors adapt the dCas9-SunTag system to engineer targeted gene activation and site-specific manipulation of DNA methylation in Arabidopsis .